Gender-Based Differences in Anxiety Levels Among Vocational High School Students When Entering the Workforce - Apriyanti Rodearnita Sinaga; Nadila Tiara Lestari; Pibreka Margaretha Br Pinem; Mukhaira EL Akmal; Sri Hartini (Faculty of Psychology, Universitas Semarang, 2025)
Not many studies have examined differences in anxiety in facing the world of work based on gender, specifically in vocational students. Previous research has conducted several studies on anxiety in vocational students. The purpose of this study is to determine the differences in the level of anxiety of vocational students towards the world of work based on their gender. The number of samples in this study was 233 students, of which 173 were male and 60 were female. This study uses a descriptive quantitative approach, with a disproportionate stratified random sampling technique and anxiety scale used to collect data. Data processing in this study uses a normality test and homogeneity test, and data analysis using a T-test by applying IBM SPSS Statistics software version 25. The results of data analysis in the T-test show a significance level value of .737(>.05), which means that there is no difference in the level of anxiety in vocational school students in facing the world of work based on gender, which means H0 is accepted, and H1 is rejected. The results of our study indicate that gender-based anxiety in the world of work in men emphasizes the abilities they have while women emphasize feelings.